THE ANALYSIS OF GOLD SAVING PRODUCT APPLICATION ACCORDING TO DECISION OF DSN-MUI NO.77/DSN-MUI/V/2010 (CASE STUDY IN PT. PEGADAIAN SYARIAH SOLO BRANCH) - Andini Rachmawati; Iman Nur Hidayat; Nunung Setiani (Universitas Darussalam Gontor, 2020)
Gold used as a currency standard in many countries and also as a medium of exchange that is relatively lasting and accepted in all countries in the world. In this case, financial institutions hold a variety of products in the context of increasing the amount of investment in gold with various forms. Especially Islamic Financial Institutions, because in Islam and it has been mentioned in the Qur’an that what is meant by assets is gold and silver including dinars.This research aims to determine the gold savings procedures and systems that are in effect and run by PT. Pegadaian Syariah Solo, and the opinions of the scholars formulated in the DSN-MUI / No. decision. 7 / V / 2010 concerning the sale and purchase of non-cash gold savings resulting in the conclusion of an analysis of gold savings products with a certified DSN-MUI review. This research was arranged using qualitative methods. The results empirically indicate that many scholars agreed that gold could be resale as terms of its goods on the grounds after the presence of banknotes society modern assume that gold now is no longer regarded as a medium of exchange but equally as well as items that can be bought and sold.